2021
DOI: 10.1161/jaha.121.020906
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Permanent Pacemaker Implantation in Patients Undergoing Transcatheter Aortic Valve Replacement ‐ A Systematic Review and Meta‐Analysis

Abstract: Background As transcatheter aortic valve replacement (TAVR) technology expands to healthy and lower‐risk populations, the burden and predictors of procedure‐related complications including the need for permanent pacemaker (PPM) implantation needs to be identified. Methods and Results Digital databases were systematically searched to identify studies reporting the incidence of PPM implantation after TAVR. A random‐ and fixed‐effects model was used to cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(94 citation statements)
references
References 133 publications
3
90
1
Order By: Relevance
“…Patients undergoing TAVI with left bundle‐branch block, right bundle‐branch block, and second‐degree heart block were more likely to be discharged on the second and third day following TAVI compared with SDD; likely because of a need for further rhythm monitoring for potential PPM implantation during the index admission. Prior studies demonstrated a higher rate of PPM implantation in patients undergoing TAVI with a preexisting bundle‐branch block 27 , 28 , 29 and may represent a cohort of patients where SDD may not be feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Patients undergoing TAVI with left bundle‐branch block, right bundle‐branch block, and second‐degree heart block were more likely to be discharged on the second and third day following TAVI compared with SDD; likely because of a need for further rhythm monitoring for potential PPM implantation during the index admission. Prior studies demonstrated a higher rate of PPM implantation in patients undergoing TAVI with a preexisting bundle‐branch block 27 , 28 , 29 and may represent a cohort of patients where SDD may not be feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Complete heart block requiring PPI within 30 days still occurs in around 10–15% of patients undergoing TAVR, even with newer generation devices. Despite notable advances in THV design and procedural technique, the rates of post-TAVR conduction disturbances have not significantly decreased over time, ranging from 4.0% to 24.0% with the Sapien 3 and from 14.7% to 26.7% with the Evolut R [ 68 ], even in the most recent years [ 69 , 70 ].…”
Section: Adverse Events After Tavrmentioning
confidence: 99%
“…Identify statistically and clinically significant factors associated with poor surgical outcomes and contextualise these factors within clinical practice. Jiang, 2021, Ullah, 2021, Van Mourik, 2020and Li, 2021 The inclusion criteria for all four reviews were similar. Only studies which included patients who underwent TAVI and reported clinical outcomes such as hospital readmission, all-cause mortality, incidence of prosthetic valve endocarditis or incidence of pacemaker implantation were included (Jiang et al, 2021;Ullah et al, 2021;Li et al, 2021;Van Mourik et al, 2020).…”
Section: Aim Of Commentarymentioning
confidence: 99%
“…Jiang, 2021, Ullah, 2021, Van Mourik, 2020and Li, 2021 The inclusion criteria for all four reviews were similar. Only studies which included patients who underwent TAVI and reported clinical outcomes such as hospital readmission, all-cause mortality, incidence of prosthetic valve endocarditis or incidence of pacemaker implantation were included (Jiang et al, 2021;Ullah et al, 2021;Li et al, 2021;Van Mourik et al, 2020). The four reviews all included randomised control trials (RCTs), with three reviews also including observational studies (Jiang et al, 2021;Ullah et al, 2021;Li et al, 2021).…”
Section: Aim Of Commentarymentioning
confidence: 99%